Internal curing of cement pastes by means of superabsorbent polymers visualized by neutron tomography. (September 2021) - Snoeck, D.; Goethals, W.; Hovind, J.; Trtik, P.; Van Mullem, T.; Van den Heede, P.; De Belie, N.
Abstract: Superabsorbent polymers (SAPs) are used to counteract self-desiccation in order to mitigate autogenous shrinkage, a problem in cementitious systems with a low water-to-cement ratio. The release kinetics during internal curing are of importance as not all SAP types are able to efficiently mitigate autogenous shrinkage. In this study, neutron tomography is used to study and visualize the water release kinetics over time. Per-voxel analysis of the time-attenuation curve was performed using piecewise-constant functions. Two different SAP types were studied, one being able to mitigate autogenous shrinkage and one quickly releasing its stored water after final setting. The tomography results correspond to autogenous shrinkage measurements and nuclear magnetic resonance tests. The visualization provides information on the time of water release by the SAPs after setting and the time window of internal curing. This opens additional insights towards the application of SAPs in the construction sector and provides information on the mechanism of internal curing. Highlights: The kinetics of water release from SAPs were studied by neutron tomography. The time window for internal curing was linked to the water release from SAPs. The water release links to the SAP effectiveness to mitigate autogenous shrinkage. One SAP type was effective while another prematurely released its stored water.